Isolation And Identification Of Bacteria That Cause Cholecystitis (Journal of Pharmaceutical Negative Results, 2022)
Objective: Isolation and identification of bacteria that cause cholecystitis by cold centrifuge method and brain heart infusion broth method.Background: This study includes isolation and identification of the microorganisms that cause cholecystitis in man, five different microorganisms isolated from forty samples taken from 40 patients after removing the infected gallbladder.Material and method: Two isolates of Staphylococcus aureus, two isolates of Listeria monocytogenes and five isolates of Escherichia coli. These microorganisms isolated by cold centrifuge method. Just one isolate of Salmonella typhi and one isolate of Shigella sonnei isolated by placing the stones found in infected gallbladders in Brain heart infusion broth for ten days from incubating at 37 Cº, Shigella sonnei isolated in the seventh day while Salmonella typhi isolated in the tenth day of incubation.To identify a bacteria; cultural, microscopic examination and Biochemical tests were done in addition to api system and antisera for diagnosis of Salmonella typhi and Shigella sonnei.Results: Samples taken from forty patients post cholecytectomy operations, five species of bacteria isolated by two methods (brain heart infusion broth method and cold centrifuge method) and cultured and identified on Macconkey, Blood, S.S, EMB, XLD, Mannitol salt, in addition to other determination tests, the isolated species of bacteria.Conclusion: Different pathogenic microorganisms from the human bile are able to cause cholecysititis and there was difficulty to isolate Salmonella typhi and Shigella sonnei from human bile because of the biofilms formed by bacteria in the gallstones.